Inequalities of opportunity in the access and use of telecommunication services in Togo. (June 2021) - Wonyra, Kwami Ossadzifo; Sanoussi, Yacobou; Sy, Ibrahima; Lanie, Tomgouani
Abstract: The liberalization of the telecommunications sector in Togo aimed at ensuring access to a better quality of telecommunication services at affordable prices to everyone. While the liberalization policy has increased competition in the sector and reduced significantly telecommunication services prices charged to costumers, statistics on the access and use of telecommunication services in Togo reveal disparities with respect to individuals' socio-economic characteristics which could be an indication of the existence of inequalities of opportunities in the access and use of these services. This paper investigates the inequalities of opportunity in the access and use of telecommunication services in Togo using a parametric approach. The results of estimations indicate that, inequalities of opportunities are larger for men and the elderly than respectively women and youths and are more pronounced in urban areas and regions such as the Plateaux and Savanna regions. Moreover, the circumstance variables such as the 'place of residence' and the 'region' are the key variables in explaining the inequalities of opportunities in the access and use of telecommunication services in Togo. So, policies toward reducing inequalities of opportunity in the access and use of telecommunication services in Togo should be designed with regards to men, the elderly, and people living in urban areas and regions such as the Plateaux and Savanna regions. Highlights: Studies on the analysis of inequality of opportunity in Togo are scanty. The state aims at insuring an access of telecommunication services at affordable price. While being women and rural resident is disadvantageous in the access of these services. Men and urban resident have experienced larger shares of inequality of opportunity.